Skeletal muscle tissue engineering - Horch, Raymund E.; et al. (Journal of Cellular and Molecular Medicine, 2004)
The reconstruction of skeletal muscle tissue either lost by traumatic injury or tumor ablation or functional damage due to myopathies is hampered by the lack of availability of functional substitution of this native tissue. Until now, only few alternatives exist to provide functional restoration of damaged muscle tissues. Loss of muscle mass and their function can surgically managed in part using a variety of muscle transplantation or transposition techniques. These techniques represent a limited degree of success in attempts to restore the normal functioning, however they are not perfect solutions. A new alternative approach to addresssing difficult tissue reconstruction is to engineer new tissues. Although those tissue engineering techniques attempting regeneration of human tissues and organs have recently entered into clinical practice, the engineering of skletal muscle tissue ist still a scientific challenge. This article reviews some of the recent findings resulting from tissue engineering science related to the attempt of creation and regeneration of functional skeletal muscle tissue.
UnivIS-Import:2015-04-14:Pub.2004.med.packli.pchw2.skelet
Keywords: Cell culture; Myoblasts; Myopathies; Satellite cells; Skeletal muscle; Tissue engineering